Effect of antiepileptic drug therapy on thyroid hormones among adult epileptic patients: An analytical cross-sectional study - Mangaiarkkarasi Adhimoolam; Ranjitha Arulmozhi (Wolters Kluwer Medknow Publications, 2016)
Objective: The objective of the study was to evaluate and compare the effect of conventional and newer antiepileptic drugs (AEDs) on thyroid hormone levels in adult epileptic patients. Methods: A hospital-based , analytical cross-sectional study was conducted among the adult epileptic patients receiving conventional AEDs (Group 2) or newer AEDs (Group 3) for more than 6 months. Serum thyroid hormone levels including free triiodothyronine (fT 3 ), free thyroxine (fT 4 ), and thyroid stimulating hormone (TSH) were analyzed and the hormonal status was compared with healthy control subjects (Group 1). Findings: Sodium valproate and phenytoin were commonly used conventional AEDs; levetiracetam and topiramate were common among the newer drugs. There was a statistically significant decrease in serum fT 4 and increase in serum TSH levels (P < 0.0001) in patients on long-term therapy with conventional antiepileptic agents than in the control group. No significant change in thyroid hormone levels (fT 3 , fT 4 , and TSH; P = 0.68, 0.37, and 0.90, respectively) was observed with newer antiepileptics-treated patients when compared to control group. One-way analysis of variance followed by post hoc Dunnett's test was performed using SPSS version 17.0 software package. Conclusion: The present study showed that conventional AEDs have significant alteration in the thyroid hormone levels than the newer antiepileptics in adult epileptic patients.